(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wijayanti C, Kuswytasari ND, Shovitri M, Danilyan E, Zulaika E. 2024. Fungal diversity in the temple with an Internal Transcribed Spacer (ITS) molecular and morphological approach. Biodiversitas 25: 2896-2906. Red bricks and andesite stones comprise most of Indonesia’s temple architecture. Red brick is a highly porous building material that weathers rapidly in temples. Physical and biological weathering are the main causes of temple weathering. Rain and other physical elements can raise the temple’s humidity, encouraging the growth of lichen and fungus. Many studies have been conducted to investigate the fungal variety in temples made of andesite stones, but the diversity found in these studies has only been identified at the genus level. This research aimed to determine the variety of fungi in the temples by employing morphological and molecular approaches like ITS biomarkers. Macroscopic characterization involves visual inspection of the colony’s color on its surface and back and its edges, texture, diameter, shape, and surface to perform morphological identification. Meanwhile, the slide culture method was used for microscopic characterization, utilizing character observations such as reproductive and hyphal structures. Several steps were involved in the molecular identification process: DNA extraction using the Genomic ex Promega Corp Wizard kit, ITS marker-based DNA amplification visualized with Gel Documenter, DNA sequencing, BLAST searches to determine the isolate species, and MEGA 11 phylogenetic tree reconstruction. Class Eurotiomycetes, which includes Talaromyces funiculosus (CB L1B isolate), Talaromyces purpureogenus (CB L3A isolate), Penicillium oxalicum (CB L4A isolate), Penicillium cataractarum (CT TL3 isolate), and Aspergillus aflatoxiformans (CT TL4 isolate), was the most prevalent among the identified species from the classes Sordariomycetes and Eurotiomycetes. Purpureocillium lilacinum (CBL1C isolate), Trichoderma anaharzianum (CB L3B isolate), and Fusarium equiseti (CT L41 isolate) were the discovered species from the Sordariomycetes class.